Noninvasive Ventilation in an Intermediate-Care-Unit - Felgueiras, Joana (2006)
Background: Non-Invasive Ventilation (NIV) is a method of alveolar ventilation, which has been shown to be effi cient and safe in patients with chronic or acute respiratory insuffi ciency. Our experience with NIV, in a Medical Intermediate-Care-Unit, over a 2-year period, is presented.Methods: A retrospective study of 66 patients who were treated with NIV, in the medical intermediate care unit (MICU) of the Garcia de Orta Hospital, between January of 2001 and December 2002 was performed. Epidemiological, clinical and laboratory data were analysed.Results: Of 315 patients admitted to the MICU, 66 (20%) were ventilated non-invasively. Fifty-three percent were male and the mean age was 68 years. The main underlying conditions leading to NIV were Chronic Obstructive Pulmonary Disease (COPD) in 33 patients (50%), Pneumonia in 12 (18%), Congestive Heart Failure (CHF) in 9 (14%), Post-Extubation-Syndrome (PES) in 6 (9%), Pickwick Disease in 4 (6%), Kyphoscoliosis and Amyotrophic Lateral Sclerosis (ALS) one of each. The interface most commonly selected for NVI was the face mask (98%). After 48 hours of ventilation, signifi cant improvement of gas exchange was achieved in 61% of patients. Nine patients deteriorated clinically within this period, of whom, three needed to be transferred to an intensive care unit for invasive ventilation and 3 patients died. The mean length of stay in the MICU was 8.5 days, with a mean time of ventilation of 6.4 days ( 8.8 in CHF, 7 in PES, 6 in COPD and 3.8 in Pneumonia). Invasive ventilation was necessary in 11 patients, 4 with COPD, 3 with pneumonia, 2 with CHF, 1 with Pickwick disease and 1 with PES. Nine percent of the patients, all suffering from COPD, continued NIV after discharge on an outpatient basis. The overall mortality of patients undergoing NIV was 21%.Conclusion and Discussion: NIV lead to signifi cant improvement in gas exchange in 61% of patients, within the fi rst 48 hours. Patients with COPD, CHF and pneumonia had the highest benefi t, the latter requiring the shortest time of ventilation.